Anatomical study of different fruit types in Argentine species of Solanum subgen. Leptostemonum (Solanaceae) - Chiarini, Franco Ezequiel (2007)
The fruits of 11 species of Solanum subgen. Leptostemonum were studied. Cross and/or longitudinal microtome sections, stained mostly with astra blue/basic fuchsin, were prepared for microscopic examination. The fruits, notably heterogeneous, were classified into three categories. Three different kinds of cells were found of the epidermis, immediately below which a hypodermis, consisting in any of five types of structures, was always found. The mesocarp presented two histologically differentiated zones, an external one (formed by normal or spongy parenchyma, depending on the species), and an internal one, commonly juicy, and with proliferations among the seeds. This morpho-anatomical information was used to distinguish between non-capsular dehiscent fruits and the berry traditionally described for Solanum. The relationship between structure and function, and the probable dispersal syndromes are also discussed.